2009
DOI: 10.1115/1.4000053
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Pin-Fin Arrays Effects on Internal Heat Transfer Enhancement of a Blade Tip Wall

Abstract: Cooling methods are strongly needed for the turbine blade tips to ensure a long durability and safe operation. Improving the internal convective cooling is therefore required to increase the blade tip life. A common way to cool the tip is to use serpentine passages with 180-deg turns under the blade tip cap. In this paper, enhanced heat transfer of a blade tip cap has been investigated numerically. The computational models consist of a two-pass channel with a 180-deg turn and various arrays of pin fins mounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The most recent work on tip cooling of gas turbine blades have received good recognition [41][42][43].…”
Section: Professor Sundén Started His Research Career In 1973 Atmentioning
confidence: 99%
“…The most recent work on tip cooling of gas turbine blades have received good recognition [41][42][43].…”
Section: Professor Sundén Started His Research Career In 1973 Atmentioning
confidence: 99%
“…Therefore, the agreement between the calculated Nusselt number and experimental data is the main criterion for selecting a turbulence model. In previous works, several turbulence models have been evaluated to simulate the turbulent heat transfer of a smooth-tip two-pass channel [29][30][31]. Based on those evaluations, the Realizable k À e turbulence model is selected for the computations in this work.…”
Section: Selection Of Turbulence Modelmentioning
confidence: 99%
“…Even though similar works of the heat transfer augmentation in two-pass channels with shaped pin-finned tips can be found in the experimental work by Bunker [28] and the numerical simulations by the authors [29][30][31][32], no available details of the heat transfer and flow field on dimpled tips are available. Furthermore, most previous studies were concerned about the heat transfer on the leading or/and trailing walls of two-pass channels, and very limited information is available for tip-walls.…”
Section: Introductionmentioning
confidence: 95%
“…The use of ribs in the internal passages of the turbine blades, the provision of arrays of pins on the turbine blade tip and the provision of dimples to the internal tip cap of the turbine blades has shown a significant increase in the heat transfer of turbine blades as far as the computations and experimental results are considered. Yet another attempt was made by Gongnan Xie et al [3] to numerically simulate the serpentine passages of turbine blade to evaluate the heat transfer but this time considering the provision of pin fins to the internal tip cap of the turbine blades. The averaged heat transfer is similar to that determined by Bunker experimentally.…”
Section: Fig 8 Performance Comparison Of Here Channelsmentioning
confidence: 99%
“…It was found that the heat transfer was doubled compared to smooth tip by provision of dimples on the surface of internal tip cap of the turbine blades. In yet another analysis Gongnan Xie [3] carried out numerical simulations for six different arrangements of the guide rib/vanes in a two pass serpentine passage. The guide ribs/vanes were placed at different locations inside the passage and their effect on the heat transfer coefficient was examined numerically using computational fluid dynamics technique.…”
Section: Fig2 a Two Pass Serpentine Passage Inside A Turbine Bladementioning
confidence: 99%